(untitled) (International Journal of Engineering and Computer Science, 2015)
Mobile ad-hoc network support dynamic topology handling due to their variable nature of communicating nodes. Here the motion of nodes is random in a specified range of the network. As the mobile nodes containlight weighted protocols for supporting transmissions, it requires some more controls over the topological aspect. The traditional topology control mechanism can be categorised according to their use like mobility sensitive, energy awareness, QoS based etc. An efficient protocol is that which dynamically handles all this issues effectively with better use of bandwidth. Problem:The aim is to investigate the shortcomings of current solutions with respect to the dynamic topology handling issues through QoS based transmissions, and bring forth new solutions to improve the performance of the network as a whole or for the individual nodes. With respect to the issue of mobility, and traffic distribution, the work focuses to investigate the factors that affect the rerouting time in proactive routing protocols. That is, the time duration needed to reroute and restore a broken communication path due to node mobility.